Central autonomic nervous system response to autonomic challenges is altered in patients with a previous episode of Takotsubo cardiomyopathy. Issue 2 (April 2016) - Pereira, Vitor H; Marques, Paulo; Magalhães, Ricardo; Português, João; Calvo, Lucy; Cerqueira, João J; Sousa, Nuno
Aims: Takotsubo cardiomyopathy is an intriguing disease characterized by acute transient left ventricular dysfunction usually triggered by an episode of severe stress. The excessive levels of catecholamines and the overactivation of the sympathetic system are believed to be the main pathophysiologic mechanisms of Takotsubo cardiomyopathy, but it is unclear whether there is a structural or functional signature of the disease. In this sense, our aim was to characterize the central autonomic system response to autonomic challenges in patients with a previous episode of Takotsubo cardiomyopathy when compared with a control group of healthy volunteers. Methods and results: Functional magnetic resonance imaging (fMRI) was performed in four patients with a previous episode of Takotsubo cardiomyopathy (average age of 67±12 years) and in eight healthy volunteers (average age of 66±5 years) while being submitted to different autonomic challenges (cold exposure and Valsalva manoeuvre). The fMRI analysis revealed a significant variation of the blood oxygen level dependent signal triggered by the Valsalva manoeuvre in specific areas of the brain involved in the cortical control of the autonomic system and significant differences in the pattern of activation of the insular cortex, amygdala and the right hippocampus between patients with Takotsubo cardiomyopathy and controls, even though these regions did not present significant volumetric changes. Conclusion: The central autonomic response to autonomic challenges is altered in patients with Takotsubo cardiomyopathy, thus suggesting a dysregulation of the central autonomic nervous system network. Subsequent studies are needed to unveil whether these alterations are causal or predisposing factors to Takotsubo cardiomyopathy.